Structural Characterization and Visible Light-Induced Photoelectrochemical Performance of Fe-Sensitized TiO2 Nanotube Arrays Prepared via Electrodeposition - Devagi, Kanakaraju; Lim Ying, Chin; Najaa, Mustaffa; Asmaa Kadim, Ayal; Lim Ying, Pei (Malaysian Institute of Chemistry, 2021)
Surface modification of TiO2 nanotube arrays via metal doping is one of the approaches to narrow the wide bandgap of TiO2 in order to increase its adsorption to the visible region. The present work focuses on the fabrication of a Fe-sensitized TiO2 nanotube arrays (Fe- TNT) photoanode. Ordered Fe-TNTs were successfully synthesized using a facile two-step electrochemical method by varying the deposition voltage (2-4 V). The morphology, structure, composition, and visible light response were characterized by field-emission scanning electron microscopy (FESEM), X-ray diffraction (XRD), energy-dispersive X-ray spectroscopy (EDX), UV-Vis diffusion reflection spectroscopy (DRS), and photoelectrochemical (PEC) test. The XRD investigation demonstrated that the sensitization of Fe did not destroy the nanotube array structure, and the Fe-TNTs had an anatase phase composed of cubic-like particles at higher deposition voltages. The UV–Vis absorption spectra of the Fe-TNTs showed a redshift of photoresponse towards visible light. Such a redshift was characterized by a decrease in bandgap energy and the photo efficiency was enhanced. The optimal photoelectrochemical performance was observed at 2.5 V deposition voltage for 10 minutes and surpassed that of pristine titania nanotube arrays. The present work demonstrates feasible modification of TiO2 with Fe as a potential photoanode in solar conversion devices.